Afferent Regulation of Inhibitory Synaptic Transmission in the Developing Auditory Midbrain - Vale, Carmen (J Neurosci, 2000)
To determine whether afferent innervation regulates the strength of inhibitory connections in the gerbil auditory midbrain, both cochleas were surgically removed in postnatal day 7 animals, before sound-driven activity is first observed. Inhibitory synaptic currents were measured in a brain slice preparation 1–7 d after the ablations. Whole-cell and gramicidin-perforated patch recordings were obtained from inferior colliculus neurons, and IPSCs were evoked by stimulation of the commissure of the inferior colliculus (CIC) or the ipsilateral lateral lemniscus (LL) in the presence of kynurenic acid. Deafferentation led to a 24 mV depolarizing shift in the IPSC equilibrium potential within 1 d of deafferentation. As a consequence, there was a large reduction of IPSC amplitude at a holding potential of −20 mV in neurons from bilaterally ablated animals. Furthermore, both afferent pathways displayed a 50% reduction of the inhibitory synaptic conductance after deafferentation, indicating that driving force was not solely responsible for the decline in IPSC amplitude. When paired pulses were delivered to the LL or CIC pathway in control neurons, the evoked IPSCs exhibited facilitation. However, paired pulse facilitation was nearly eliminated after deafferentation. Thus, normal innervation affects inhibitory synaptic strength by regulating postsynaptic chloride homeostasis and presynaptic transmitter release properties.